Entre « chic » et « chien » : les séductions de la Parisienne, de Jean-Jacques Rousseau à Yves Saint-Laurent - Emmanuelle Rétaillaud-Bajac (Genre, Sexualité et Société)
This paper aims to analyse the appearance and evolution of the image of « la Parisienne », a central character in the reputation of the capital of France, often depicted as elitist and pleasure-seeking. Starting in the 18th century, and more specifically from Rousseau’s reflections, we show how « la Parisienne » was very early defined by her love of fashion and talent for seducing men. Elaborated in the context of a monarchist society opening up to modern capitalism, this portrait became more complex and visible in the following century as the city itself changed very fast along with the explosion of the popular press and shifts in symbolic and aesthetic regimes. Today, though the image and reputation of « la Parisienne » are still used in the advertisement business and as a journalistic cliché, they have largely lost their subversive and erotic character due to the « sexual revolution » of the 1960’s and the homogenisation of behaviour in western societies.